Manufacturing of Open-Cell Metal Foams by the Sponge Replication Technique. Issue 1 (July 2020) - Sutygina, A; Betke, U; Hasemann, G; Scheffler, M
Abstract: Different manufacturing techniques for open-cell metal foams, such as investment casting and space holder casting, are compared with the sponge replication technique that is originally used for the preparation of ceramic foams. Processing of aluminum foams by the sponge replication technique has been reviewed. Based on the results obtained for aluminum open-cell foams, the feasibility of copper foam manufacturing with the sponge replica technique using an aqueous copper dispersion was demonstrated.